Peran Guru PAI Dalam Peningkatan Kedisiplinan Siswa Di SMPN 2 Mojoagung Jombang - Nirwana, Arum Sutra; Mujahidin, Mujahidin (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
The teacher has the responsibility to see everything that happens in the classroom to help the student's development process. The teacher is someone who is able to carry out educational actions in an educational situation or a person who is mature, honest, patient, physically and mentally healthy, virtuous, expert, skilled, open, fair and compassionate. Therefore teachers need to accustom students to live regularly by always being given exemplary and coaching related to discipline. Being a PAI teacher in carrying out his role is supposed to instill the values ??of discipline in students, because discipline has an integral part of the legitimacy of religious worship. The aims of this study are 1. To describe the role of Islamic education teachers in improving student discipline at SMPN 2 Mojoagung Jombang. 2. To describe the form of student discipline at SMPN 2 Mojoagung Jombang. This study uses qualitative research using data collection techniques through observation, interviews, and documentation. The results of this study indicate that: 1. The role of PAI teachers in improving student discipline. As for the teacher as a motivator, the teacher as a guide, as well as the driving factor for the teacher in increasing student discipline at SMPN 2 Mojoagung. 2. The application of student discipline at SMPN 2 Mojoagung Jombang, namely the habituation method and the punishment method.